The National Undergraduate Neuroanatomy Competition: Lessons Learned from Partnering with Students to Innovate Undergraduate Neuroanatomy Education. (June 2019) - Geoghegan, Kate; Payne, December R.; Myers, Matthew A.; Hall, Samuel; Elmansouri, Ahmad; Parton, William J. C.; Harrison, Charlotte H.; Stephens, Jonny; Parker, Rob; Rae, Shivani; Merzougui, Wassim; Nagy, Eva; et al.
Undergraduates often perceive neuroscience to be a challenging discipline. As the scope of neuroscience continues to expand, it is important to provide undergraduates with sufficient opportunities to develop their knowledge and skills with the aim of encouraging the future generation of basic and clinical neuroscientists. Through our experience of developing the National Undergraduate Neuroanatomy Competition (NUNC), we have accrued an extensive volume of performance data and subjective insight into the delivery of undergraduate neuroanatomy education, which has the potential to inform how to better engage students within this field. More broadly, our group has implemented a technology enhanced learning platform alongside a peer-assisted teaching program. These achieve the dual purpose of compensating for the reduction in dedicated neuroanatomy teaching hours and encouraging undergraduates to develop an interest in the neurosciences. Here, we consider how improving the learning experience at an undergraduate level encourages further engagement in the neurosciences and the importance of this within the wider neuroscience community.